2012
DOI: 10.1139/y2012-102
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 7 polarizes THP-1 cells into M2 macrophages

Abstract: It was hypothesized that monocyte treatment with bone morphogenetic protein 7 (BMP7) would significantly enhance monocyte polarization into M2 macrophages as well as increasing the levels of anti-inflammatory cytokines. In a cell culture system using monocytes (human acute monocytic leukemia cell line THP-1), we studied the effects of BMP7 on monocytes polarizing into M2 macrophages. The data demonstrate that THP-1 cells contain a BMP type II receptor (BMPR2), and that its activation is significantly (p < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 11 publications
5
54
2
Order By: Relevance
“…Furthermore, whether the effect of BMP7 on macrophage polarisation is either direct or indirect, in response to changes in BAT, remains to be determined. Although we could not show in our in vitro experiments a direct effect of BMP7 on M1/M2 skewing in bone-marrow derived macrophages, a recent study in which human THP-1 monocytes were treated with BMP7 demonstrated significant polarization of monocytes into M2 macrophages [30]. However, since the change in M1/M2 balance did not happen at thermoneutral temperature suggests that environmental factors are at least in part involved in the effects of BMP7 on macrophage polarisation.…”
Section: Discussioncontrasting
confidence: 84%
“…Furthermore, whether the effect of BMP7 on macrophage polarisation is either direct or indirect, in response to changes in BAT, remains to be determined. Although we could not show in our in vitro experiments a direct effect of BMP7 on M1/M2 skewing in bone-marrow derived macrophages, a recent study in which human THP-1 monocytes were treated with BMP7 demonstrated significant polarization of monocytes into M2 macrophages [30]. However, since the change in M1/M2 balance did not happen at thermoneutral temperature suggests that environmental factors are at least in part involved in the effects of BMP7 on macrophage polarisation.…”
Section: Discussioncontrasting
confidence: 84%
“…BMP6 regulates expression of inflammatory markers such as IL-6, IL-1β, and nitric oxide synthase in macrophages [7880]. In addition, more recent studies indicate that BMP exposure particularly leads to the M2 or anti-inflammatory phenotype of the macrophages promoting tissue repair [8184]. Microglia are descendants of immature macrophages and are thought to act as macrophages in disease and injury states [85].…”
Section: Discussionmentioning
confidence: 99%
“…The slides were counterstained with DAPI, and then were then incubated at 4°C for 24 hours. Cells were photomicrographed using confocal microscopy and cell counting was preformed, as we reported previously (Rocher et al 2012;Singla et al 2014).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…These pro-inflammatory cytokines include IL-6, MCP-1, and TNF-α (Kleemann et al 2008;Outtz et al 2010;Singla et al 2014). Conversely, M2 macrophages are anti-inflammatory, and aid in the repair of damaged tissue, making them a potential candidate for therapeutic options (Rocher et al 2012;Singla et al 2016). Secreted from M2 macrophages are the anti-inflammatory cytokines IL-10 and IL-1RA, and show an increase in the expression of Arginase-1 enzyme important in reducing harmful nitric oxide production (Kleemann et al 2008;Outtz et al 2010;Singla et al 2014).…”
mentioning
confidence: 99%